2022
DOI: 10.1177/87552930221129636
|View full text |Cite
|
Sign up to set email alerts
|

Ground motion simulation for the 21 May 2021 Ms 6.4 Yangbi, China, earthquake using stochastic finite-fault method

Abstract: On 21 May 2021, a 6.4-magnitude earthquake occurred in Yangbi County, Yunnan Province, China. To reproduce the ground motion characteristics of this earthquake, the stochastic finite-fault method was adopted. The ground motion records were analyzed to determine the source, path, and site parameters. Based on the optimization algorithm, the stress drop was set to 10 bar. The S-wave attenuation relation ( QS = 122.7 f0.44) was calculated by the spectral decay method. For the site effect, the site amplification w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The focal mechanism solution given by the Global Centroid Moment Tensor showed that the magnitude of the Yangbi mainshock was Mw 6.1, and it was a strike-slip earthquake. Studies have shown that the Yangbi earthquake occurred in an NW-SE right rotation strike-slip secondary fault on the west side of the Weixi-Qiaohou Fault in the north section of the Honghe Fault (Qiang et al, 2021). The Honghe Fault is the southwest boundary of the Sichuan-Yunnan rhombic block in the southeast of the Qinghai-Tibet Plateau.…”
Section: Recordings Of the Yangbi Earthquakementioning
confidence: 99%
See 1 more Smart Citation
“…The focal mechanism solution given by the Global Centroid Moment Tensor showed that the magnitude of the Yangbi mainshock was Mw 6.1, and it was a strike-slip earthquake. Studies have shown that the Yangbi earthquake occurred in an NW-SE right rotation strike-slip secondary fault on the west side of the Weixi-Qiaohou Fault in the north section of the Honghe Fault (Qiang et al, 2021). The Honghe Fault is the southwest boundary of the Sichuan-Yunnan rhombic block in the southeast of the Qinghai-Tibet Plateau.…”
Section: Recordings Of the Yangbi Earthquakementioning
confidence: 99%
“…The baseline correction and the cosine window are added at the beginning and end of the recording waveform to eliminate the recording error, and then the Butterworth non-causal band-pass filter (0.08-30 Hz) is applied to process the records. As one of the essential input parameters, and the effective frequency band of the recordings after filter process is 0.1-24 Hz (Qiang et al, 2021). The source model of the Yangbi earthquake was established using the scaling law based on global and local source parameters and truncated normal distribution density function (Dang, Cui, Liu, & Ji, 2023;Wang, 2004), as shown in Figure 2.…”
Section: Recordings Of the Yangbi Earthquakementioning
confidence: 99%
“…The 2021 M s 6.4 Yangbi earthquake with moment magnitude 6.1 occurred at the intersection of the Red River and Weixi-Qiaohou-Weishan faults, in a region of western Yunnan Province with complex mountain topography (see Figure 2). It is the largest earthquake occurred in this region in the past 45 years (Wang et al, 2023). Epicenter of this strike-slip earthquake is located at latitude 25.67°N, longitude 99.87°E.…”
Section: Introductionmentioning
confidence: 99%
“…However, they require accurate input-model parameters to produce a ground-shaking pattern that matches the specific characteristics of real regional records. Once these methods are calibrated with input-model parameters specific to a region of interest, they can serve as powerful tools for assessing the potential impact of future earthquake hazards and disasters [16].…”
Section: Introductionmentioning
confidence: 99%